THE ROLE OF SOCIAL INSTITUTIONS AS AGENTS OF SOCIALIZATION IN DEVELOPING EDUCATIONAL QUALITY - Rakhmat; Annisa Auwla Rahma; Tutuk Ningsih (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to explore the role of social institutions as agents of socialization in developing educational quality. This research uses qualitative research with a descriptive approach. The qualitative approach was chosen to deeply understand social phenomena related to the role of social institutions as socialization agents in developing educational quality. Through this approach, researchers can explore comprehensive information regarding processes, roles, and interactions within the social environment affecting education. The descriptive approach provides systematic, factual, and accurate descriptions of field conditions, focusing not only on outcomes but also on how social institutions perform their roles in the socialization of educational values. This research was conducted in communities connected with educational institutions, including schools, families, and surrounding communities. The research location was selected purposively considering active interactions among social institutions. The research subjects include parents, teachers, community leaders, religious leaders, and students, while the research object is the role of social institutions as agents of socialization in developing educational quality, including their roles, contributions, and challenges. The results indicate that improving educational quality cannot be carried out partially but must involve various social institutions in an integrated manner. Quality education is education that integrates cognitive, affective, and psychomotor aspects through support from a conducive social environment. Thus, social institutions do not only function as complementary elements but also as main components in the educational system. Strengthening the role of social institutions has an impact on improving the quality of competitive and character-driven human resources.